A-29 Consistency of Clinical Profiles Across Repeat Concussions. (13th July 2022) - Manderino, L M; Preszler, J; French, J; Kegel, N; Blaney, N; Collins, M W; Kontos, A P
Abstract: Purpose: To evaluate the association between concussion profiles within individual patients across repeat concussions. Methods: Retrospective chart review of 100 adolescents (57.3% male) aged 10–21 years presenting to a concussion clinic within 30 days of injury for two separate injuries between 2011 and 2021. Clinicians conducted multidomain assessments including vestibular/ocular motor screening, neurocognitive testing, symptoms and medical/injury history to adjudicate the following concussion clinical profiles: vestibular, ocular, post-traumatic migraine, cognitive fatigue, and anxiety/mood. Chi-square tests with odds ratios (OR) and 95% confidence intervals (CI) were conducted to examine the association of each profile from the first to the second concussion. Results: Chi-square analyses supported associations between the first and second concussions (time between injuries = 667.1 ± 529.2 days) for the vestibular (χ 2 = 10.08, p < 0.01, OR = 3.75, 95% CI = 1.63–8.62), ocular (χ 2 = 6.51, p < 0.05, OR = 3.51, 95% CI = 1.30–9.46), and migraine (χ 2 = 11.056, p < 0.001, OR = 4.01, 95% CI = 1.73–9.29) profiles, such that having that profile at first concussion was associated with increased likelihood of having the same profile at second concussion. Chi-square analyses for cognitive fatigue and anxiety/mood were not significant. Conclusions: Vestibular, ocular, and migraine profiles at first injury predicted their presence at second injury, which may reflect consistent underlying risk factors (e.g., sex migraine history) for these profiles. Conversely, no association was supported for anxiety/mood and cognitive fatigue profiles across injuries. The present findings are the first to demonstrate that certain profiles are likely to recur after repeat concussion. This information can be used by clinicians to inform earlier, targeted treatment recommendations for associated profiles.